Curcumin modulates TLR4/NF-κB inflammatory signaling pathway following traumatic spinal cord injury in rats. (March 2015) - Ni, Hongbin; Jin, Wei; Zhu, Tiansheng; Wang, Jing; Yuan, Baoyu; Jiang, Jian; Liang, Weibang; Ma, Zhengliang
Abstract : Background: Curcumin, a polyphenolic compound extracted from the plant turmeric, has protective effects on spinal cord injury (SCI) through attenuation of inflammatory response. This study was designed to detect whether curcumin modulates toll-like receptor 4 (TLR4) and the nuclear factor-kappa B (NF-κB) inflammatory signaling pathway in the injured rat spinal cord following SCI. Methods: Adult male Sprague–Dawley rats were subjected to laminectomy at T8–T9 and compression with a vascular clip. There were three groups: (a) sham group; (b) SCI group; and (g) SCI + curcumin group. We measured TLR4 gene and protein expression by real-time polymerase chain reaction and western blot analysis; NF-κB activity by electrophoretic mobility shift assay, inflammatory cytokines tumor necrosis factor-α, interleukin-1β, and interleukin-6 levels by enzyme-linked immunosorbent assay, hindlimb locomotion function by Basso, Beattie, and Bresnahan rating, spinal cord edema by wet/dry weight method, and apoptosis by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) analysis. Results: The results showed that SCI induced the up-regulation of TLR4, NF-κB, and inflammatory cytokines in the injured rat spinal cord. Treatment with curcumin following SCI markedly down-regulated the levels of these agents related to the TLR4/NF-κB inflammatory signaling pathway. Administration of curcumin also significantly ameliorated SCI induced hind limb locomotion deficits, spinal cord edema, and apoptosis. Conclusions: Post-SCI curcumin administration attenuates the TLR4/NF-κB inflammatory signaling pathway in the injured spinal cord, and this may be a mechanism whereby curcumin improves the outcome following SCI.